The Undergraduate Training in Genomics (UTRIG) Initiative: early & active training for physicians in the genomic medicine era. (30th May 2018) - Wilcox, Rebecca L; Adem, Patricia V; Afshinnekoo, Ebrahim; Atkinson, James B; Burke, Leah W; Cheung, Hoiwan; Dasgupta, Shoumita; DeLaGarza, Julia; Joseph, Loren; LeGallo, Robin; Lew, Madelyn; Lockwood, Christina M; et al.
Genomic medicine is transforming patient care. However, the speed of development has left a knowledge gap between discovery and effective implementation into clinical practice. Since 2010, the Training Residents in Genomics (TRIG) Working Group has found success in building a rigorous genomics curriculum with implementation tools aimed at pathology residents in postgraduate training years 1–4. Based on the TRIG model, the interprofessional Undergraduate Training in Genomics (UTRIG) Working Group was formed. Under the aegis of the Undergraduate Medical Educators Section of the Association of Pathology Chairs and representation from nine additional professional societies, UTRIG's collaborative goal is building medical student genomic literacy through development of a ready-to-use genomics curriculum. Key elements to the UTRIG curriculum are expert consensus-driven objectives, active learning methods, rigorous assessment and integration.